Environment-behavior studies for healthcare design - Ding, Suining (New York, NY : Routledge, 2023)
"Environment-Behavior Studies for Healthcare Design explains how environment-behavior (EB) studies can contribute to healthcare design research and explores how evidence-based theories can be applied and integrated into the healthcare design practice. Drawing on EB theories and the latest research in environment-behavior studies, this book shows how the healthcare environment can positively impact patients' and caregivers' well-being and healthcare organization's efficiency by modifying environmental attributes, such as space configuration, color, and lighting, signage, acoustics, and artwork. It addresses a range of healthcare facilities including children's hospitals, long-term care, acute care and outpatient care facilities, and uses a range of evidence-based design research methods, such as interviews, focus groups, observations, surveys and space syntax. The author also explains how research evidence and evidence-based design can be integrated into healthcare design more cohesively in a redefined design process. This book provides a solid conceptual structure that informs a clear map for understanding the EB theories and their applications in healthcare design. This research guide for healthcare design helps students, academics, designers and architects reconsider how to create environments that support patients' healing and well-being whilst considering efficiency and safety"--Provided by publisher.
Keywords: Health facilities -- Design and construction; Hospital buildings -- Design and construction; Environmental psychology; ARCHITECTURE / General; ARCHITECTURE / Design & Drafting; ARCHITECTURE / Interior Design / General